PENGARUH KEPEMIMPINAN CAMAT TERHADAP DISIPLIN KERJA APARATUR SIPIL NEGARA DI KECAMATAN NAMORAMBE KABUPATEN DELI SERDANG - Pin Pin; Reno Girsang (JURNAL GOVERNANCE OPINION, 2021)
Leadership is a process and activity that continues to develop so that individuals who are led carry out organizational activities according to the expected goals. The role of leaders in an organization is a measure of the success of the organization. Appropriate leadership can affect the process of an organization's activities towards achieving the desired goals. This study aims at (i) determining whether the leadership of the Head of Sub-District has an effect on the work discipline of the State Civil Apparatus in Namorambe District, Deli Serdang Regency. (ii) finding out what are the supporting factors and obstacles to the work discipline of the State Civil Apparatus in Namorambe District, Deli Serdang Regency. The form of this research is quantitative research. This research was conducted in the office of the Namorambe District, Deli Serdang Regency. Data collection techniques are through library research and field research. Types and sources of data carried out in this study are primary data and secondary data. The results of this study illustrate that the leadership of the sub-district head has a significant influence on the work discipline of the State Civil Apparatus in Namorambe District, Deli Serdang Regency. This is in accordance with the Pearson and Spearman's Rho correlation coefficient, which is between 0.40-0.70. The good relationship that was built by the Head of Sub-district, consistent sanctions and clear instructions were the supporting factors for the discipline